A multi-parameter investigation of elite archery: distinguishing individual and shared performance strategies during the aiming and follow-through phases - Jacquot, Raphaël; Ben Mansour, Khaireddine; Bouillet, Kévin; Jehl, Jean-Philippe; Gauchard, Gérôme (Frontiers in Sports and Active Living, 2025)
IntroductionArchery accuracy relies heavily on the aiming and follow-through phases, during which factors such as muscle activation, postural control, and drawing arm movement play key roles. This study aims to assess whether these performance determinants in high-level archery are consistent across athletes or reflect individual-specific strategies.MethodsEight top-level French archers (4 women, 4 men) shot eight rounds of nine arrows at a 70 m target, using their personal equipment in a competition-like outdoor setting. Data on neuromuscular activity, postural control, body segment configuration and temporal strategies were collected during the aiming and follow-through phases. Arrow scores were grouped into high (10), mid (9), and low (≤8) for analysis.ResultsAt the group level, several muscles and postural control parameters were associated with performance during the aiming phase (seven muscles, three postural parameters, and mechanical clicker reaction time) and the follow-through phase (four muscles and three postural parameters). At the individual level, two parameters during aiming (medial deltoid activity on the bow side and aiming duration) and two parameters during the follow-through phase (upper trapezius activity on the drawing side and surface of center of pressure displacement) were identified as individual strategies.DiscussionThese findings highlight both shared performance determinants and individualized strategies among elite archers, emphasizing that while technical approaches vary, certain biomechanical patterns remain crucial for optimal performance.